Wide crossing in African Vigna species - Fatokun, C.A.; Perrino, P.; Ng, N.Q. (1997)
The genus Vigna comprises seven subgenera and sixteen sections. Cowpea, Vigna tingnicnlatti (L.) Walp.. is an important grain legume crop in sub-Saharan Africa and belongs to the subgenus Vigna. section Ctitiang. Morphologically, cowpea genotypes appear very variable. However, a high level of genome homology exists among the varieties and this, probably, is because genomes of cowpca's wild relatives have not been exploited while these varieties were being developed. Cowpea varieties are susceptible to some insect pests, especially the pod borer. Manica vitrata, and a podsucking bug complex, both of which can cause high seed yield losses. Accessions of some wild Vigmi species, e.g. V. oblong/folia and V vexillata, are known to be resistant to these pests, and efforts continue lo be made, through wide crossing, to transfer the resistance genes from these species to cultivated cowpea. So far cowpea has been successfully crossed only to genotypes belonging in section Catiang. Among the noncultivated African Vigna .vpecies. there have been successful crossesm between V. oblongifolia and Iwo others. V. ambacensis and V. lureola. Although the hybrids are only partially fertile. Embryo rescue was used to recover an F| interspecific hybrid between V. oblongifolia and V. luieola. All three species belong to section Vigna of the subgenus Vigna. A successful cross has also been carried out between V. davyi and V. vexillaia, both members of the subgenus Plectoiropis